Jean Baptiste Colbert – A Theorist and a Practitioner - Pladis, Benjaminas; Jasilionis, Augustinas (Lithuanian Journal of Statistics, 2010)
The main purpose of this article is to analyse the theoretical and practical work of Jean Baptiste Colbert – the grandee of French economics and the representative of mercantilism. This article deals with almost all areas of his work: state economy, trade policy, national defence, culture and art. This article mainly focuses on economics. First of all, the article widely analyses the works of J. B. Colbert in the area of tax reform. Colbert focused on the shift in the tax load from the poor onto the prosperous, not forgetting the simplification of tax administration. The ideas of Colbert, which remained purely theoretic, are introduced alongside. In addition, Colbert focused on the industrial development of the country. The State promoted the establishment of manufactories, high-skilled labour imports, estimated the quality standards of production, aimed at the effective administration of supplies. Moreover, an effort was made to restrict imports and expand exports, as well as to establish transatlantic trade companies. At the end of the article, other activities of Colbert and changes in the situation after he passed away are briefly analysed. This article is topical for today’s realities. Recent turmoil both in the global and in the national economy stimulates the search for analogies and methods of how similar situations were handled in the past.